O devido processo legal e as serventias extrajudiciais no contexto da desjudicialização: a relação entre as garantias fundamentais da segurança jurídica e do acesso à justiça. - Alves Neto, Jocy de Vasconcelos Frota (2021)
The search for the effectiveness of the guarantee of a due and fair process in the contemporary Democratic State of Law rests not only on the fact that only judges and courts, in the jurisdictional path, would be bound by the normative content of the general clause of the due process of law. The state agents in general would be, each in the performance of their functions, and here are included the extrajudicial services, also representatives of the State in the prevention and resolution of conflicts, when exercising their mission, also acting as enforcers of a material right guaranteed by the in the same Constitution? The principle of due legal process, conceived as a fundamental guarantee of the citizen in the face of state action, has its spectrum of application extended to all branches - or doors - available in the legal system, as well as to any and all State actions, therefore, also in extrajudicial administrative activity. The present work will analyze the principal influence that the guarantees of due process of law and legal security began to have repercussions on the extrajudicial action of notarial and registry services, notably from the phenomenon of de-judicialization. Starting from a new conception of access to justice, revealed as the fundamental right to a fair legal order, and therefore to the Justice System as a whole, transcending the classic idea of strict formal access to the Judiciary. In view of this new legal scenario arising from the de-judicialization and the growing dissemination of extrajudicial means of conflict resolution, in which the administrative process has been strengthened as an instance for the realization of material rights, it is clear that administrative agents would be able to enforce the guarantees and constitutionally guaranteed fundamental rights. The performance of the services would also take place from the lens of due legal process as a compass to indicate the direction of legal security, an organic principle that guides any and all processes/procedures. The result of the investigation reveals that the extrajudicial registries reveal themselves with institutional characteristics and purposes capable of achieving access to a fair legal order. The method used in this research as the most appropriate methodological path, considering the proposed objectives, paradigms and axiological nuclei of a constitutional order, consisted of bibliographical and dogmatic research, based on a literature review on access to material justice and due process of law. substantial in comparison with the postulates of legal security in the environment of de-judicialization in Brazil and in the international scenario.